Sintomas de insônia em indivíduos pós-ave crônico: caracterização e potenciais preditores - Ruani Araújo Tenório (2021)
Background: Insomnia is defined by the difficulty in falling asleep or maintaining sleep despite the opportunity and adequate time, for at least 3 times a week, for at least 3 months and, therefore, resulting in daytime impairment. Around 70% of individuals in the acute phase and 40% in the post-stroke chronic phase experience problems related to sleep, these being excessive daytime sleepiness, fatigue and insomnia. Sleep performs important functions such as tissue restoration and clearing brain metabolites of neurotoxic potentials, waste products that accumulate during wakefulness. Studies have shown an association between sleep disorders and disability, presence of depressive symptoms, fatigue and compromised quality of life. For the diagnosis of sleep disorders, it is necessary to take as a basis the individual's clinical presentation and exams such as polysomnography and specific questionnaires. Currently, most studies on the prevalence and interference of sleep disorders in the functional recovery of individuals refer to the acute post-stroke phase, when in a hospital environment. However, few studies on sleep disorders in individuals in the chronic phase have been carried out. It is necessary to consider these after stabilization of neurological symptoms and after hospital discharge, with the individual in their usual environment. In this way, the influence of unstable neurological conditions and environmental factors is avoided. Objective: To characterize a sample of post-stroke individuals regarding the presence of insomnia complaints and to determine whether the variables age, independence in activities of daily living, walking ability, depression, fatigue and quality of life could explain the presence of insomnia complaints in the chronic phase. Method: This is a cross-sectional and exploratory study, approved by the Research Ethics Committee of the Federal University of Minas Gerais, under CAAE 02465118.9.0000.5149. Sample composed of individuals who met the following inclusion criteria: aged ≥ 20 years; clinical diagnosis of stroke for at least six months; ability to walk independently, being able to use walking aid devices; absence of cognitive alterations identified by the Mini-Mental State Examination. The research consisted of a single evaluation stage, in which personal information, sociodemographic, clinical and anthropometric data were collected to characterize the sample. The independent variables were age, independence in activities of daily living measured by the Modified Rankin Scale, ability to walk using the 6-minute walk test, depression measured by the Geriatric Depression Scale, fatigue measured by the Fatigue Severity Scale, and quality of life measured by the visual scale of EuroQol. The presence of insomnia complaints, defined as a dependent variable, was measured by the Insomnia Severity Index (ISI). Binary logistic regression analysis was used to identify variables which may explain the presence of insomnia complaints in this population. Results: 90 participants were included in the study, with a mean age of 61 (12) years; 55 (61%) were male and the average time between the stroke and the interview was 58.2 (58.7) months. Twenty-eight participants (31%) had ISI scores equal to or greater than 10, suggesting the presence of symptoms of insomnia. The mean ISI score was 7.58 (SD 5.47). In the regression analysis, statistically significant associations were found between insomnia complaints and depressive symptoms (r = 0.322; p = 0.002), independence in activities of daily living (r = 0.231; p = 0.028), fatigue (r = 0.270; p = 0.010) and quality of life (r = -0.234; p = -0.026). No significant association was found between insomnia complaints and walking ability (r = -0.091; p = 0.387; p> 0.10). Therefore, depressive symptoms, functional status, fatigue and quality of life were included in the logistic regression analysis. Among the four variables inserted into the model, only depressive symptoms (GDS) were retained. Depressive symptoms explained 73% (OR 1.2; 95% CI 1.1-1.4) of the variance in insomnia complaints. Conclusion: Depressive symptoms were determinants of the presence of post-stroke insomnia complaints. It is important to consider the assessment of sleep quality in the context of rehabilitation of these individuals and, when possible, intervene in associated modifiable factors.